Contemporary art and critical perspectives in industrial design education. Issue 2 (3rd July 2017) - Kaya Pazarbasi, Cigdem
Abstract: In this article, the transforming impact of two contemporary art related elective courses offered to sophomore and senior industrial design students at an undergraduate industrial design program is examined. Increasing discussions indicate that industrial designers' practice field is expanding, requiring them to pay more attention to the ecological and societal concerns impacting commons while improving use experience towards Industry 4.0. These concerns are reflected upon the educational material. In this article it is argued that exposing industrial design students to contemporary art as part of their curriculum can have an extended impact on how they perceive industrial design as part of a bigger contextual practice framework containing ecological and societal values rather than mere market concerns. In this research, responses to the introduced contemporary art related content were collected based on 48 semi-structured student interviews and student work. A thematic analysis of the reports indicated that the students' learning experiences in the electives contributed to their self-perception as industrial designers and had a role in constructing the meaning and aim of their future professional identity.